Morphological analysis of puzzles are riddles - J.Hiyal, Abdul-Reda. (Journal of College of Education, 2021)
Puzzles in the arabic morphology is described as the most complex puzzles in the Arabic language, It’s because that the same puzzle has it’s mysteries and vagueness, Other than the fact that the arabic morphology is a difficult science and isn’t easy to it’s students, and it has been agreed upon that to the morphological puzzles two difficult things, first of which is the mystery of the puzzle, secondly is the difficulty of the art that the puzzle is portrayed as. And this study unveils these two different subjects, and analyzing a sentence of the morphological puzzles in the arabic language.